Modeling of biomass-based hydrogen production via catalytic sorption-enhanced reformer integrated with a gasifier - Yucel, Ozgun; Aydin, Ebubekir Siddik (Elsevier, 2023)
The sorption enhanced reformer concept breaks the thermodynamic limits of steam methane reforming and water-gas shift reactions with selective CO2 removal to produce more H2. In this paper, we propose a dynamic kinetic model for sorption-enhanced steam reformers (SERs) integrated with biomass gasifiers. An analysis of operating conditions was conducted to examine high purity hydrogen production. The kinetic model was vali-dated with published literature results at different reactor pressures (5-20 bar), steam/carbon ratios (2-5), and reactor temperatures (673K-1023K). This study shows that biomass gasifiers can be integrated with SER reactors to produce high purity H2.
Keywords: Modeling; Hydrogen; Gasification; Sorption enhanced reforming; Energy